2021
DOI: 10.1017/s0007114521001859
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Module design in Maintain Your Brain: an internet-based randomised controlled trial to prevent cognitive decline and dementia

Abstract: The Maintain Your Brain trial (MYB) is one of the largest internet-delivered multidomain RCT designed to target modifiable risk factors for dementia. It comprises four intervention modules: physical activity, nutrition, mental health, and cognitive training. This paper explains the MYB Nutrition Module, which is a fully online intervention promoting the adoption of the ‘traditional’ Mediterranean Diet (MedDiet) pattern for those participants reporting dietary intake that does not indicate adherence to a Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…The fully online nutrition module promotes the adoption of the Mediterranean diet and is administered to participants who report dietary intakes that do not align with the Mediterranean diet or those who have chronic disease risk factors and may benefit from dietary change. The findings from this trial are expected to be available in 2023 and are expected to provide further evidence regarding the value of digital health technologies for delivering dietary interventions and facilitating behaviour change in older adults [75].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The fully online nutrition module promotes the adoption of the Mediterranean diet and is administered to participants who report dietary intakes that do not align with the Mediterranean diet or those who have chronic disease risk factors and may benefit from dietary change. The findings from this trial are expected to be available in 2023 and are expected to provide further evidence regarding the value of digital health technologies for delivering dietary interventions and facilitating behaviour change in older adults [75].…”
Section: Discussionmentioning
confidence: 94%
“…Another study found that dietary counselling provided by a dietitian through a smartphone app led to increased adherence to the Mediterranean diet, comparable to traditional in-person counselling [27]. The Maintain Your Brain trial is a web-based multidomain intervention targeting modifiable risk factors for dementia [75]. The fully online nutrition module promotes the adoption of the Mediterranean diet and is administered to participants who report dietary intakes that do not align with the Mediterranean diet or those who have chronic disease risk factors and may benefit from dietary change.…”
Section: Discussionmentioning
confidence: 99%
“…A good learning system could be used to increase patient compliance AD clinical trials as well. There are numerous examples for utility of these elements in other fields [ [120] , [121] , [122] , [123] ]. Another creative question could be “Do internet-delivered methods of cognitive enhancement influence the gut-brain axis?“.…”
Section: Microbiota Modulation Influences Molecular Mechanisms Throug...mentioning
confidence: 99%
“…Digital health technologies are increasingly being utilised in the management and treatment of a range of health conditions, including diabetes, 15 healthy eating habits, 16 obesity, 17 sleep, 18 physical activity 19 and depression and anxiety. 20 However, few have been developed specifically for older adults, representing a largely untouched area for potential technologies to improve the health and wellbeing of older adults in Australia and globally.…”
Section: Introductionmentioning
confidence: 99%